PENDAMPINGAN PEMAHAMAN PEMIKIRAN NASR HAMID ABU ZAID TERHADAP POLIGAMI PERSPEKTIF AL-QUR’AN DI MAJLIS TA’LIM MUSLIMAT BEKASI - Abd. Rohim; Hamdani Anwar; Ahmad Thib Raya; Ilya Syafa’atun Ni’mah; Imam Addauqutni; Misbahul Huda (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Polygamy is one of the important issues in the renewal of Islam and feminist movements, call it Amina Wadud, Riffat Hassan, Nazaruddin Umar, Musdah Mulia in this contemporary era. various forms of methods and theories were used by these figures in an attempt to reinterpret the polygamous verses in the Qur'an. One of them is the interpretation of polygamy using the Hermeneutic perspective of Nasr Hamid Abu Zayd. This perspective interprets polygamy verses historically-critically-contextually rooted in holistic methods (maudhu'i).